Hepatitis C Screening in an Underserved U.S. Cohort of Reproductive Age Women. Issue 9 (11th July 2019) - Kim, Nicole J.; Holguin, Daniel; Bush, Dylan; Khalili, Mandana
Abstract : The opioid epidemic has recently increased the rates of hepatitis C virus (HCV) infection among young women. We therefore aimed to characterize the cascade of HCV care in a cohort of underserved women of reproductive age. Medical records of 19, 121 women between the ages of 15 and 44 years, receiving primary care in the San Francisco safety‐net health care system, were reviewed. Cohort characteristics were as follows: median age 33 years (interquartile range 26‐38), 18% white (12% black, 46% Latina, 22% Asian, 2% other race), 1.3% hepatitis B surface antigen (HBsAg)‐positive, and 0.9% human immunodeficiency virus (HIV) co‐infection. HCV antibody (HCVAb) testing occurred in 38.7% (n = 7, 406), of whom 2.8% (n = 206) were HCVAb‐positive and 2.4% (n = 177) had a detectable HCV viral load. Of the 5% (n = 1, 017) with a history of pregnancy, 61% (n = 615) had HCVAb testing (2.6% were positive). On multivariable analysis, HBsAg testing (odds ratio [OR] 8.25 [95% confidence interval (CI)] 6.80‐10.01]; P  < 0.001), HIV infection (OR 5.98 [95% CI 1.86‐19.20]; P  = 0.003), and log alanine aminotransferase (ALT) (OR 1.30 [95% CI 1.16‐1.45]; P  < 0.001) were associated with HCV screening. Compared with whites, women of Latina (OR 0.45 [95% CI 0.37‐0.55]; P  < 0.001) and Asian (OR 0.74 [95% CI 0.58‐0.94]; P  = 0.01) race were less likely to receive HCV screening. Age (OR 1.80 per decade [95% CI 1.26‐2.57]; P  = 0.001), white race (versus non‐white; OR 10.48 [95% CI 7.22‐15.21]; P  < 0.001), HIV infection (OR 3.25 [95% CI 1.40‐7.55]; P  = 0.006), and log ALT (OR 1.93 [95% CI 1.49‐2.49]; P  < 0.001) were associated with HCVAb positivity. Conclusion: Most (>60%) underserved women of reproductive age were not tested for HCV. Moreover, women of Latina and Asian race were less likely to receive HCV screening. Given the known high HCV risk in the underserved population, targeted interventions, especially for racial minority women of reproductive age, are needed to enhance HCV screening in those at risk. Abstract : We aimed to characterize the cascade of hepatitis C virus (HCV) care in a cohort of underserved women of reproductive age. Most (more than 60%) underserved women of reproductive age were not tested for HCV, and women of Latina and Asian race were less likely to receive HCV screening. Targeted interventions, especially for racial minority women of reproductive age, are needed to enhance HCV screening rates in this at‐risk population.